2021
DOI: 10.3389/fgene.2021.638980
|View full text |Cite
|
Sign up to set email alerts
|

A Glycolysis-Based Long Non-coding RNA Signature Accurately Predicts Prognosis in Renal Carcinoma Patients

Abstract: BackgroundThe prognosis of renal cell carcinoma (RCC) varies greatly among different risk groups, and the traditional indicators have limited effect in the identification of risk grade in patients with RCC. The purpose of our study is to explore a glycolysis-based long non-coding RNAs (lncRNAs) signature and verify its potential clinical significance in prognostic prediction of RCC patients.MethodsIn this study, RNA data and clinical information were downloaded from The Cancer Genome Atlas (TCGA) database. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
(29 reference statements)
0
13
0
Order By: Relevance
“… Xing et al (2021 ) found that LINC02609 was associated with the OS of patients with KIRC. Cao et al (2021 ) found that the glycolysis-related lncRNA AC124854.1 was markedly correlated with the OS of renal cancer by univariate and multivariate Cox regression analyses. Cheng et al (2019 ) also found that AC124854.1 could be used as a prognostic and diagnostic biomarker for KIRC.…”
Section: Discussionmentioning
confidence: 99%
“… Xing et al (2021 ) found that LINC02609 was associated with the OS of patients with KIRC. Cao et al (2021 ) found that the glycolysis-related lncRNA AC124854.1 was markedly correlated with the OS of renal cancer by univariate and multivariate Cox regression analyses. Cheng et al (2019 ) also found that AC124854.1 could be used as a prognostic and diagnostic biomarker for KIRC.…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental examination is needed to explore the interaction network in the future. Notably, in these twelve EMT-related lncRNAs, AC084876.1 has been identified as glycolysis-related lncRNA with prognostic value in KIRC by Cao et al [ 43 ]. IL10RB-DT has been reported associated with immune infiltration in KIRC [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microenvironment of various cell clusters involved in cancer has become a hot topic in recent years [ 23 ]. We found 9 types of tumor invasive immune cells from the expression level of CCNB1 in BC.…”
Section: Discussionmentioning
confidence: 99%
“…By using expression analysis and correlation analysis, the most potential upregulated lncRNAs AC026401.3 was identified ( Figure 4D , 4E ). Glycolysis based AC026401.3 have important value in survival prediction of renal cell carcinoma patients [ 23 ], but their specific roles in tumors are unclear and deserve further exploration [ 33 ].…”
Section: Discussionmentioning
confidence: 99%